Assessment of the possibility of forecasting hydrometeorological extremes using the solar activity index - Miskevich I.V.; Kotova E.I. (Российская Арктика, 2023)
The paper presents the results of research of correlation fields of the relationship between Wolf number and hydrometeorological parameters (air and water temperature, annual precipitation, snow cover height) for a number of points in the western sector of the Russian Arctic (Norilsk, Indiga, Unsky Mayak, Kholmogory). Wolf numbers are used as an indicator of solar activity. It is proposed to determine the recurrence of the sought extremum on the scattering diagram for each interval of Wolf numbers with a length of 25 units. Correlation fields have a quasi-triangular shape or a combination of a quasi-rectangle and a triangle. The highest probability of geoecological anomalies is observed in the range of Wolf numbers “0-125”. At the further increase of values probability appreciably decreases. Under geoecological anomalies in this case the authors mean natural events on the surface of the Earth with a frequency of less than 10%, which can entail disastrous consequences for ecosystems, its individual regions or local zones. For economic activity, which has risks of emergency situations due to the influence of hydrometeorological processes, the most "calm" years are typical for the period of maximum solar activity, the most "disturbing" years are typical for the period of minimum solar activity. In the presence of nonlinear configuration of scattering diagram boundaries in the plots of solar-terrestrial relations, we can use one-dimensional regression models with preliminary linearization of such relations. In this case, the reliability of determining the error of the predictions increases. Statistical analysis of correlation fields divided on certain intervals of solar activity allows obtaining forecasts of hydrometeorological extremes capable of forming geoecological anomalies in a number of situations. The method can be used for specifying longterm hydrometeorological and ecological forecasts. This approach can be used as an alternative way of detecting geoecological anomalies.